2013
DOI: 10.1155/2013/276972
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Oscillation Analysis for a Coupled FHN Network Model with Delays

Abstract: The existence of periodic oscillation for a coupled FHN neural system with delays is investigated. Some criteria to determine the oscillations are given. Simple and practical criteria for selecting the parameters in this network are provided. Some examples are also presented to illustrate the result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Recently, some criteria to determine the periodic oscillation were provided in the multiple delayed FHN neural system with three nonidentical cells [19]. In [20], the Hopf bifurcation and Bogdanov-Takens bifurcation were investigated in a coupled FHN neural system with gap junction.…”
Section: Abstract and Applied Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some criteria to determine the periodic oscillation were provided in the multiple delayed FHN neural system with three nonidentical cells [19]. In [20], the Hopf bifurcation and Bogdanov-Takens bifurcation were investigated in a coupled FHN neural system with gap junction.…”
Section: Abstract and Applied Analysismentioning
confidence: 99%
“…The simple zero singularity (both pitchfork and transcritical bifurcations) was studied employing the center manifold reduction and normal form method [17]. Further, by applying the Bautin bifurcation theorem, the coexistence of rest state and periodic spiking was reported in the synchronous solution of a coupled FHN neural system with delay [18].Recently, some criteria to determine the periodic oscillation were provided in the multiple delayed FHN neural system with three nonidentical cells [19]. In [20], the Hopf bifurcation and Bogdanov-Takens bifurcation were investigated in a coupled FHN neural system with gap junction.…”
mentioning
confidence: 99%
“…In the actual nerve conduction process, there is a certain time delay in signal transmission, which caused a lot of research on the FHN model with time delay. Wang et al studied bifurcation and synchronization ( 1 ), bifurcation structure ( 2 ), Fold-Hopf bifurcation ( 3 ), periodic oscillation ( 4 ), and global Hopf bifurcation ( 5 ) of coupled FHN model with time delay. Yu et al ( 6 ) found that the noise level can change the signal transmission performance in the FHN network, and the delay can cause multiple stochastic resonances.…”
Section: Introductionmentioning
confidence: 99%
“…The stability and oscillation of the solutions is investigated by constructing of Liapunov functional and applying the Chafees limit cycle criterion. Zhen and Xu [42] and also Lin [50] generalized the FHN models to a three coupled FHN neurons and Feng and Plamondon [51] to a four coupled FHN neurons with time delay. They derived some criteria to determine the periodic oscillation were provided in the multiple delayed FHN neural system with nonidentical cells.…”
Section: Introductionmentioning
confidence: 99%